Meteorological Data at Japanese Ny-Ålesund Observatory, Svalbard in 1994 and 1995 - アオキ, シュウジ; ナカニシ, ユウジ; ワダ, マコト; ヤマノウチ, タカシ; Aoki, Shuhji; Nakanishi, Yuji; Wada, Makoto; Yamanouchi, Takashi (National Institute of Polar Research, 1996)
P(論文) Dataset : Meteorological Data at Japanese Ny-Alesund Observatory, Svalbard in 1994 and 1995. | https://ads.nipr.ac.jp/dataset/A20131010-003 departmental bulletin paper